Location of the Fracture Faces Within the Cell Envelope of Acinetobacter Species Strain MJT/F5/5 - Sleytr, U. B. (1974)
The cell wall of the gram-negative bacterium Acinetobacter species strain MJT/F5/5 shows in thin section an external “additional” layer, an outer membrane, an intermediate layer, and a dense layer. Negatively stained preparations showed that the additional layer is composed of hexagonally arranged subunits. In glycerol-treated preparations, freeze-etching revealed that the cell walls consist of four layers, with the main plane of fracture between layers cw 2 and cw 3. The surface of [Formula: see text] 2 consisted of densely packed particles, whereas [Formula: see text] 3 appeared to be fibrillar. In cell envelopes treated with lysozyme by various methods, the removal of the dense layer has detached the outer membrane and additional layer from the underlying layers, as shown in thin sections. When freeze-etched in the absence of glycerol, these detached outer membranes with additional layers fractured to reveal both the faces [Formula: see text] 2 and [Formula: see text] 3 with their characteristic surface structures, and, in addition, both the external and internal etched surfaces were revealed. This experiment provided conclusive evidence that the main fracture plane in the cell wall lies within the interior of the outer membrane. This and other evidence showed that the corresponding layers in thin sections and freeze-etched preparations are: the additional layer, cw 1; the outer membrane, cw (2 + 3); and the intermediate and dense layers together from cw 4. Because of similarities in structure between this Acinetobacter and other gram-negative bacteria, it seemed probable that the interior of the outer membrane is the plane most liable to fracture in the cell walls of most gram-negative bacteria.